Waves and Swells in High Wind and Extreme Fetches, Measurements in the Southern Ocean - Babanin, Alexander V.; Rogers, W. Erick; de Camargo, Ricardo; Doble, Martin; Durrant, Tom; Filchuk, Kirill; Ewans, Kevin; Hemer, Mark; Janssen, Tim; Kelly-Gerreyn, Boris; Machutchon, Keith; McComb, Peter; et al. (Frontiers in Marine Science, 2019)
The generation and evolution of ocean waves by wind is one of the most complex phenomena in geophysics, and is of great practical significance. Predictive capabilities of respective wave models, however, are impaired by lack of field in situ observations, particularly in extreme Metocean conditions. The paper outlines and highlights important gaps in understanding the Metocean processes and suggests a major observational program in the Southern Ocean. This large, but poorly investigated part of the World Ocean is home to extreme weather around the year. The observational network would include distributed system of buoys (drifting and stationary) and autonomous surface vehicles (ASV), intended for measurements of waves and air-sea fluxes in the Southern Ocean. It would help to resolve the issues of limiting fetches, extreme Extra-Tropical cyclones, swell propagation and attenuation, wave-current interactions, and address the topics of wave-induced dispersal of floating objects, wave-ice interactions in the Marginal Ice Zone, Metocean climatology and its connection with the global climate.